THE EFFECT OF LANGUAGE LEARNING STRATEGY TRAINING ON STUDENTS’ ENGLISH DESCRIPTIVE READING AND DESCRIPTIVE WRITING ACHIEVEMENTS OF THE TENTH GRADE STUDENTS OF SMAN 1 TANJUNG BATU - Whinda Riesmayani (ELTE Journal (English Languange Teaching and Education), 2014)
ABSTRACT The objective of this study is to know the use of language learning strategy training affect in the achievement of students’ descriptive reading and descriptive writing. The population of this study was all the tenth grade students of SMA Negeri 1 Tanjung Batu in the academic year of 2012/2013 consisting of 186 students. From population, 60 students were taken as a sample using simple random sampling. In carrying out the research, the writer used pre-test-post-test control group design. In analyzing the data, the writer used the t-test (paired sample and independent sample t-test) and were calculated by SPSS Version 17. Based on the result of the data analysis by using independent sample t-test, it was found that (1) p-output was 0.000 and is lower than the mean significant difference at the 0.05 level. It means that H1 is accepted (2) p-output was 0.000 and is lower than the mean significant difference at the 0.05 level. It means that H2 is accepted (3) p-output was 0.01 and is lower than mean significant difference at the 0.05 level. It means that H3 is accepted. It means that there was significant difference in students’ descriptive reading and descriptive writing achievement of the students who were taught through language learning strategy training compared to those who were not. It proved that language learning strategy training affect to students reading and writing achievements. Keywords: Language Learning Strategy Training, Descriptive Reading, Descriptive Writing